Building with nature : creating, implementing and upscaling nature-based solutions - Eekelen, Erik van; Bouw, Matthijs (EcoShape ; One Architecture ; Rotterdam : nai010 publishers, 2020)
"Building with Nature is a proven, innovative approach to create water-related Nature-based Solutions for societal challenges, that harnesses the forces of nature to benefit the environment, economy and society. EcoShape, a unique collaboration between scientists, engineers, builders, designers and not-for-profits, has in the past decade designed, realized, monitored and researched multiple Building with Nature projects in Europe (especially in the Netherlands) and South East Asia. These projects demonstrate the capacity to build Nature-Based Solutions at scale to create safe and sustainable flood protection as well as ecologically rich and resilient environments that provide great places to live, work, and visit. These characteristics make Building with Nature the go-to method to adapt to and mitigate climate change. In this book, EcoShape brings the authors into dialogue with experts and stakeholders to discuss methodologies and lessons learned about Building with Nature as well as potential barriers and enablers for implementation. It describes and illustrates key concepts, linking them to a range of landscape types and their underlying ecological, economic, and social systems. As such, the book is more than a manual; it captures the imaginative and inspirational potential of Building with Nature"--Page 4 cover.